Waiting for thyroid surgery: A study of psychological morbidity and determinants of health associated with long wait times for thyroid surgery1. (2nd August 2012) - Eskander, Antoine; Devins, Gerald M.; Freeman, Jeremy; Wei, Alice C.; Rotstein, Lorne; Chauhan, Nitin; Sawka, Anna M.; Brown, Dale; Irish, Jonathan; Gilbert, Ralph; Gullane, Patrick; Higgins, Kevin; et al.
Abstract Objectives: Patients with thyroid pathology tend have longer surgical wait times. Uncertainty during this wait can have negative psychologically impact. This study aims to determine the degree of psychological morbidity in patients waiting for thyroid surgery. Study Design: Prospectively assessing patients pre‐ and postoperative psychological morbidity (level 2c). Methods: Patients waiting for thyroidectomy were mailed a sociodemographic and four psychological morbidity questionnaires: Impact of Events Scale–Revised (IES‐R), Illness Intrusiveness Ratings Scale (IIRS), Perceived Stress Scale (PSS) and Hospital Anxiety and Depression Scale (HADS). We assessed whether anxiety was related to length of wait and a number of clinical/sociodemographic factors. RESULTS: We achieved a 53% response rate over a 3‐year period, with 176 patients providing complete preoperative data; and 74 (42%) completed postoperative data. The average age was 53 (±12) years; 82% were female. Respondents with a suspicious or known malignancy waited an average of 107 days while those with benign neoplastic biopsies waited an average of 218 days for thyroidectomy. Respondents reported substantial psychological morbidity with high IES‐R, IIRS, PSS, and HADS scores. There was no significant association between psychological morbidity and wait times, clinical or sociodemographic factors. Postoperative anxiety decreased significantly in all psychological morbidity measures except for the IIRS. Conclusions: Patients waiting for thyroid surgery have mild to moderate psychological morbidity and long wait times for surgery. These appear not to be related. Psychological morbidity decreases after surgery. Reducing wait time can potentially reduce the time that patients have to live with unnecessary stress and anxiety. Laryngoscope, 2012